ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP OPINI AUDIT GOING CONCERN - Thio Anastasia Petronila (Jurnal Bisnis dan Ekonomi, 2007)
The objective of this study is to explore audit opinion, which is auditor responsibilities to Asses, a client’s ability to continue as a going concern. The dependent variable (audit opinion) is a dummy variable representing the presence of absence of a Going Concern Audit Report (GCAR). Independent variables consist of corporate governance mechanism analysis focuses on Board of Commissioner changes, board of directur schanges, board of commissioner or directors ownership, auditor quality, and risk. The hypotheses proposed were tested by binary logistic show that board of commissioner changes, board of directors changes, board of commissioner and/or directors ownership, and risk is significant, auditor quality that the result is not significant to the audit opinion . Keywords: Going Concern Audit Report, Corporate Governance Mechanism, Board of Directur Changes, Board of Commissioner, Directors Ownership, Auditor Quality, Risk.